The key that swallowed Joey Pigza - Gantos, Jack. (New York : Farrar, Straus Giroux, 2014)
"Everything goes topsy-turvy for Joey as he becomes the man of the house, looking after his new baby brother, taking care of his troubled mother, and seeking out his missing father"--
Keywords: Attention-deficit hyperactivity disorder -- Fiction; Single-parent families -- Fiction; Babies -- Fiction; Brothers -- Fiction; Attention-deficit hyperactivity disorder -- Juvenile fiction; Single-parent families -- Juvenile fiction; Infants -- Juvenile fiction; Brothers -- Juvenile fiction